Spectra of algebras of analytic functions, generated by sequences of polynomials on Banach spaces, and operations on spectra - Vasylyshyn, S.I. (Carpathian Mathematical Publications, 2023)
We consider the subalgebra of the Fréchet algebra of entire functions of bounded type, generated by a countable set of algebraically independent homogeneous polynomials on the complex Banach space X. We investigate the spectrum of this subalgebra in the case X = _1. We also consider some shift type operations that can be performed on the spectrum of this subalgebra in the case X = _p with p ≥ 1.